Formulations for Bacteriophage Therapy and the Potential Uses of Immobilization - Daniel Rosner; Jason Clark (MDPI AG, 2021)
The emergence of antibiotic-resistant pathogens is becoming increasingly problematic in the treatment of bacterial diseases. This has led to bacteriophages receiving increased attention as an alternative form of treatment. Phages are effective at targeting and killing bacterial strains of interest and have yielded encouraging results when administered as part of a tailored treatment to severely ill patients as a last resort. Despite this, success in clinical trials has not always been as forthcoming, with several high-profile trials failing to demonstrate the efficacy of phage preparations in curing diseases of interest. Whilst this may be in part due to reasons surrounding poor phage selection and a lack of understanding of the underlying disease, there is growing consensus that future success in clinical trials will depend on effective delivery of phage therapeutics to the area of infection. This can be achieved using bacteriophage formulations instead of purely liquid preparations. Several encapsulation-based strategies can be applied to produce phage formulations and encouraging results have been observed with respect to efficacy as well as long term phage stability. Immobilization-based approaches have generally been neglected for the production of phage therapeutics but could also offer a viable alternative.